Engineering carrier scattering at the interfaces in polyaniline based nanocomposites for high thermoelectric performances. (1st November 2016) - Wang, Liming; Yao, Qin; Shi, Wei; Qu, Sanyin; Chen, Lidong
Abstract : Ternary PANI/SWNT/Te nanocomposite films with high thermoelectric properties were obtained through the rational design of nanostructures and energy barriers. Abstract : We have developed a novel strategy to in situ synthesize water-soluble ternary PANI/SWNT/Te nanocomposites with uniform structures and high thermoelectric (TE) properties. An abnormally high Seebeck coefficient was obtained for the ternary PANI/SWNT/Te nanocomposite films due to the energy filtering effect at the interfaces of PANI/SWNTs and PANI/Te, while the electrical conductivity still remained relatively high. As a result, the TE power factor of the ternary composite films was up to 101 μW m −1 K −2, which was much higher than that of the individual components (PANI, SWNTs and Te nanorods). Moreover, a TE module made up of the ternary PANI/SWNT/Te nanocomposite films was fabricated, which was able to generate a high power density of 62.4 μW cm −2 . Our results reveal a successful approach through designing the nanostructures and energy barriers of ternary nanocomposites to improve the TE properties of PANI.